Validity of social–emotional screening tool for newborns and infants: The effects of gender, ethnicity and age - Antoniou, Faye; Al-Khadim, Ghadah S. (Frontiers in Psychology, 2022)
The purpose of the present study was to test the measurement invariance of the baby pediatric symptom checklist (BPSC) across gender and age as a means to provide for valid comparisons in point estimates across groups. A secondary goal involved confirming the earlier identified factor structure and re-examining the presence of differentially item functioning in the BPSC across grouping variables. Participants were 601 children (322 boys and 279 girls) aged below 1 year (n = 294) and 1 year to 12 months (n = 307). Data were collected as part of the National Health Interview Survey in 2020. Results related to gender indicated satisfying all five levels of measurement and structural invariance. When testing measurement invariance across age groups, a few modifications were necessary. Specifically, partial metric invariance was satisfied after freeing slope estimates of items 1 and 2, partial scalar after freeing intercept terms of items 6 and 10, and partial residual invariance through freeing error terms of items 2 and 12. These non-invariant estimates, however, provide support for partial invariance and do not invalidate the comparison of latent means. The BPSC can be used for the valid assessment of social–emotional skills in infants up to the age of 18 months.